Development of nanoparticle-assisted PCR assay in the rapid detection of brain-eating amoebae - Gabriel, Shobana *; Rasheed, A. K. *; Siddiqui, Ruqaiyyah Bano *; Appaturi, Jimmy Nelson; Leo, Bey Fen (Springer Verlag, 2018)
Brain-eating amoebae (Acanthamoeba spp., Balamuthia mandrillaris, Naegleria fowleri) have gained increasing attention owing to their capacity to produce severe human and animal infections involving the brain. Early detection is a pre-requisite in successful prognosis. Here, we developed a nanoPCR assay for the rapid detection of brain-eating amoebae using various nanoparticles. Graphene oxide, copper and alumina nanoparticles used in this study were characterized using Raman spectroscopy measurements through excitation with a He–Ne laser, while powder X-ray diffraction patterns were taken on a PANanalytical, X’Pert HighScore diffractometer and the morphology of the materials was confirmed using high-resolution transmission electron microscopy (HRTEM). Using nanoparticle-assisted PCR, the results revealed that graphene oxide, copper oxide and alumina nanoparticles significantly enhanced PCR efficiency in the detection of pathogenic free-living amoebae using genus-specific probes. The optimal concentration of graphene oxide, copper oxide and alumina nanoparticles for Acanthamoeba spp. was determined at 0.4, 0.04 and 0.4 μg per mL respectively. For B. mandrillaris, the optimal concentration was determined at 0.4 μg per mL for graphene oxide, copper oxide and alumina nanoparticles, and for Naegleria, the optimal concentration was 0.04, 4.0 and 0.04 μg per mL respectively. Moreover, combinations of these nanoparticles proved to further enhance PCR efficiency. The addition of metal oxide nanoparticles leads to excellent surface effect, while thermal conductivity property of the nanoparticles enhances PCR productivity. These findings suggest that nanoPCR assay has tremendous potential in the clinical diagnosis of parasitic infections as well as for studying epidemiology and pathology and environmental monitoring of other microbes.